Assessment of Nurses’ Knowledge, Attitude, and Practices on Antibiotic Use and Resistance in Baghdad: A single-hospital study - Habib, Kholod Dhaher; Jaber, Zainab Ali; Hassan, Abbas Abboud (AL-Kindy College Medical Journal, 2022)
Background: There are so many evidences that there was antimicrobial resistance, and there were many strains that emerged which were difficult to treat. We are living in a situation that the dissemination of multiple drug resistant bacteria can lead us to the situation, in which no treatment could be offered for bacterial infection in future.Aim of study: Assessment of nurses’ knowledge, attitude, and practices on antibiotic use and resistance in Fatima Al Zahra hospital in Baghdad.Subjects and Methods:  A cross-sectional study. The study was carried on from 1st of February to 31st of March 2021.  A questionnaire was constructed by the research team based on literature review and was adapted to assess the nurses’ knowledge, attitude, and practices on antibiotic use and resistance in Fatima Al Zahra hospital. The adopted questions were mainly based on previous studies carried out in Lebanon, and Ethiopia. It was piloted among 10 nurses. The questionnaire was further revised by the research team. The final questionnaire contained 26 questions on the following: Demographics characteristics (5 questions), Knowledge of antibiotics (7 questions), Attitude towards antibiotic use (7 questions); and practice with regards to antibiotic use (7 questions). Analysis plan: IBM SPSS (Statistical Package for the Social Sciences) Statistics version 21 Multilingual and Microsoft Excel 2010 were used to analyze the data. The frequencies were stated first then Chi-Square test and Fisher’s exact test were used to investigate the association. The p-value less than 0.05 were considered significant.Results: One hundred and eight nurses participated in this study, of whom 101 (93.5%) were female, 31(28.7%) of participants at the age group of (18-27) years, 33(30.6%) were at the age group of (28-37) years, with mean age 26± 0.54 SD. Regarding the highest qualification, 41(38%) graduated from the high school of nursing, 35(32.4%) graduated from the midwife school. About 46(42.6%) of the participants were working in pediatric words, and 23(21.3%) were working in gynecology and obstetrics (Gyn & Obs) words. There was gap in the knowledge especially in nurses who had lowest qualification: 44(40%), of them believe that using antibiotic in cold can speed recovery and 41 (38%) believe that antibiotic can cure viral infections, and 42(38.9%), of them consider that newer and more costly antibiotics affect better.Conclusion: There was a gap in nurse’s knowledge, and practice, towards the antibiotic use and antibiotic resistance, the Current work place was the most effective factor in this gap.